Distinct Metagenomic Signatures in the SARS-CoV-2 Infection - Yijun Liu (Frontiers Media S.A., 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can cause gastrointestinal symptoms in the patients, but the role of gut microbiota in SARS-CoV-2 infection remains unclear. Thus, in this study, we aim to investigate whether SARS-CoV-2 infection affects the composition and function of gut microbiota. In this study, we demonstrated for the first time that significant shifts in microbiome composition and function were appeared in both SARS-CoV-2-infected asymptomatic and symptomatic cases. The relative abundance of Candidatus_Saccharibacteria was significantly increased, whereas the levels of Fibrobacteres was remarkably reduced in SARS-CoV-2-infected cases. There was one bacterial species, Spirochaetes displayed the difference between patients and asymptomatic cases. On the genus level, Tyzzerella was the key species that remarkably increased in both symptomatic and asymptomatic cases. Analyses of genome annotations further revealed SARS-CoV-2 infection resulted in the significant ‘functional dysbiosis’ of gut microbiota, including metabolic pathway, regulatory pathway and biosynthesis of secondary metabolites etc. We also identified potential metagenomic markers to discriminate SARS-CoV-2-infected symptomatic and asymptomatic cases from healthy controls. These findings together suggest gut microbiota is of possible etiological and diagnostic importance for SARS-CoV-2 infection.